Exploring Esp Instruction Through Systemic Functional Linguistics - Kokok Dj Purwanto; Dwi Rorin Mauludin (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2024)
Most of the students have found difficulties in understanding ESP course so far, because they are lack of English comprehension or they are not quite interested in the subject. Thus, they get unsatisfied score in the first evaluation. By understanding the SFL framework in the context of ESP instruction, they will explore the role of register and genre in language use and analysis because SFL plays  a crucial role in language instruction for learners who need to use English in their academic and professional contexts.This study examines  the ESP pedagogy through the lens of Systemic Functional Linguistics (SFL) and applies for the SFL perspective to ESP pedagogy. It is used a case study in qualitative terms where able to enhance the understanding of the language features, discourse structure and communicative purposes. It is emphasizing the importance of teaching language for specific purposes, functional linguistic and discourse analysis in professional contexts. The key concepts of SFL, such as the metafunctions of language (interpersonal, ideational and textual), and how these can shed light on the communicative purposes on ESP Instruction and language choices within ESP textbooks.